2004
DOI: 10.1002/ijc.20737
|View full text |Cite
|
Sign up to set email alerts
|

Potential immunogenicity of adult T cell leukemia cells in vivo

Abstract: Experimental vaccines targeting human T cell leukemia virus type-I (HTLV-I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…Our observations were qualitatively identical in donors who were asymptomatic, and those with inflammatory conditions. Our findings are also in agreement with those of Kurihara et al who showed that cultured PBMC from two patients with Adult T cell Leukaemia/Lymphoma (ATL) stimulated stronger responses than PBMCs from uninfected donors in a mixed lymphocyte reaction [38]. These changes in cellular phenotype were only observed after in vitro culture, and were not detected in fresh peripheral blood samples.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations were qualitatively identical in donors who were asymptomatic, and those with inflammatory conditions. Our findings are also in agreement with those of Kurihara et al who showed that cultured PBMC from two patients with Adult T cell Leukaemia/Lymphoma (ATL) stimulated stronger responses than PBMCs from uninfected donors in a mixed lymphocyte reaction [38]. These changes in cellular phenotype were only observed after in vitro culture, and were not detected in fresh peripheral blood samples.…”
Section: Discussionsupporting
confidence: 93%
“…[42][43][44] To investigate whether Tax-specific CTLs were induced in HTLV-1-infected mice, the IBMI-huNOG mice were generated using hematopoietic stem cells purified from the cord blood of an HLA-A*24:02 haplotype individual. HLA-A*24:02 tetramers coupled with Tax301-309 were used to detect CTLs.…”
Section: Induction Of Htlv-1-specific Adaptive Immune Responses In Htmentioning
confidence: 99%
“…Consequently, a large number of MHC class I -restricted CTL epitopes derived from the Tax protein have been identified (6,13,14,20). However, we believe that the CD4 + helper T lymphocytes (HTL) also play an important role in HTLV-1 infection because HTLs are required for clonal expansion of antibodysecreting B cells and induction and maintenance of optimal CTL responses (21,22). Moreover, in some instances, HTLs can exhibit an effector function by directly recognizing and killing MHC class II + virus-infected or tumor cells that present peptide epitopes on their surface (23 -26).…”
mentioning
confidence: 99%